2015
DOI: 10.1111/1440-1681.12406
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of mechanisms involved in the vasorelaxation produced by rosuvastatin in aortic rings from rats with a cafeteria‐style diet

Abstract: The present study aimed to investigate the possible influence of several inhibitors and blockers on the vascular effect produced by the acute in vitro application of rosuvastatin to phenylephrine-precontracted aortic rings from rats with a semi-solid, cafeteria-style (CAF) diet. It also aimed to examine the effects of rosuvastatin on the expression of endothelial nitric oxide synthase (eNOS), inducible nitric oxide synthase, constitutive cyclooxygenase, and inducible cyclooxygenase in aortic rings from rats wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…The vasorelaxant effect of rosuvastatin in the present study was partially attenuated in vessels pre-incubated with L-NAME, indomethacin or glipenclamide indicating that, endothelial nitric oxide (NO), prostaglandin and ATP-sensitive K channel are involved in its vasorelaxant effects. These results are in agreement with the study done by Lopez-Canales et al (2011) and Lopez-Canales et al (2015).…”
Section: Discussionsupporting
confidence: 94%
“…The vasorelaxant effect of rosuvastatin in the present study was partially attenuated in vessels pre-incubated with L-NAME, indomethacin or glipenclamide indicating that, endothelial nitric oxide (NO), prostaglandin and ATP-sensitive K channel are involved in its vasorelaxant effects. These results are in agreement with the study done by Lopez-Canales et al (2011) and Lopez-Canales et al (2015).…”
Section: Discussionsupporting
confidence: 94%
“…The CAF-diet is a robust experimental model of metabolic syndrome that is capable of inducing obesity, glucose intolerance, and inflammation in rats (7,9), and is consistent with the results of our experiments, which showed that the 16-week CAFdiet significantly increased (Po0.05) body weight, serum insulin, glucose, total cholesterol, and triglycerides in Wistar rats (Table 1). These findings reinforced previous studies in which an 8-week CAF-diet increased the same metabolic parameters in Wistar rats (4) and are in line with previous reports linking a high-fat diet to increases in levels of glucose, cholesterol, triglycerides, and insulin (10,11).…”
Section: Discussionsupporting
confidence: 92%
“…Seventy-two male Wistar rats were purchased from the Escuela Superior de Medicina (Mexico), housed in plastic cages in a special temperature-controlled room (22 ± 2°C, 50% humidity), and kept on a 12-h light/dark cycle (lights on at 7 am). They were randomly distributed into three groups that received for 16 weeks: i) a standard diet (Rat chow 5012, Pet Foods Home, Mexico); ii) a CAF-diet containing 33% ground commercial rat chow, 33% full-fat sweetened condensed milk (Nestlé), 7% sucrose, and 27% water (n=36), as reported by López-Canales et al (4); or iii) a CAF-diet plus rosuvastatin administered orally (10 mg/kg) once per day. All animals had free access to drinking water throughout the experiments.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations